RVAD implantation in a Fontan patient with protein‐losing enteropathy as a bridge to transplant: Prêtre modification. Issue 7 (19th June 2020) - Moosmann, Julia; Dittrich, Sven; Purbojo, Ariawan; Cesnjevar, Robert
Abstract: Fontan patients with protein‐losing enteropathy (PLE) represent poor candidates for cardiac transplantation due to end‐organ injury and severely impaired clinical condition. Ventricular assist device (VAD) therapy has evolved as a promising bridge to transplant strategy improving quality of life and survival on the waiting list. However, VAD therapy for the Fontan circulation remains challenging. For Fontan patients with preserved ventricular function implantation of a right ventricular assist device (RVAD) has been described by Prêtre et al as bridge to transplant. We present the second case of RVAD support in a Fontan patient with PLE.